The effect of nitric oxide synthase blockade and indometacin on gastric emptying and gastric contractility - YEGEN, BERRAK (KARGER, 1997)
The aim of the present study was to investigate the effect of nitric oxide (NO) synthase inhibition on gastric emptying rate in conscious rats and on gastric muscle contractility. The involvement of NO was also investigated in indometacin-induced (25 mg/kg, s.c.) changes in gastric emptying rate and smooth muscle contractility. L-NAME (N-G-nitro-L-arginine methyl ester; 10 mg/kg, i.v.) inhibited the gastric emptying rate compared to controls and this effect was abolished by L-arginine (300 mg/kg, i.v.). Similarly, indometacin treatment led to a significant delay of gastric emptying rate with respect to vehicle-treated rats. Gastric longitudinal and circular muscle strips of L-NAME or indometacin-treated rats showed a reduction in contractile responses to carbachol. The results demonstrate that NO synthase blockade and indometacin treatment delay gastric emptying in conscious rats, concomitant with reduced responsiveness to carbachol, in vitro.
Keywords: indometacin; nitric oxide; gastric emptying; gastric contractility; NO synthase blockade; carbachol; NONADRENERGIC NONCHOLINERGIC NERVES; ARGININE METHYL-ESTER; MUSCLE-CELLS; STIMULATION; RELEASE; FUNDUS; RATS; NEUROTRANSMISSION; CYCLOOXYGENASE; RELAXATION